2007
DOI: 10.1007/s11172-007-0348-x
|View full text |Cite
|
Sign up to set email alerts
|

Planar chiral hydroxy derivatives of [2.2]paracyclophane as auxiliaries for asymmetric allylboration

Abstract: Allylboronic esters with various structures were synthesized for the first time based on [2.2]paracyclophane derivatives containing one or two hydroxy groups. It was demonstrated that these esters can be used as chiral inductors in the asymmetric allylboration of benzalde hyde. The highest enantiomeric excess of 1 phenylbut 3 en 1 ol (60%) was achieved in the reactions with acyclic bis O,O´ (paracyclophanyl) allylboronates based on (S) 4 hydroxy and (S) 12 bromo 4 hydroxy[2.2]paracyclophanes. (S) 4 Hydroxy[2.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A Suzuki coupling of enantiopure ( S P )‐ 20 with 2‐hydroxyphenyl boronic acid ( 21 ) gave the diol ( S P )‐ 22 in 70% yield (Scheme ). This compound has been mentioned in the literature several times,27–29 but no characterization has been published so far.…”
Section: Resultsmentioning
confidence: 99%
“…A Suzuki coupling of enantiopure ( S P )‐ 20 with 2‐hydroxyphenyl boronic acid ( 21 ) gave the diol ( S P )‐ 22 in 70% yield (Scheme ). This compound has been mentioned in the literature several times,27–29 but no characterization has been published so far.…”
Section: Resultsmentioning
confidence: 99%
“…ester adducts formed upon treatment with activated camphanoyl derivatives. [54][55][56][57][58][59][60] This quite general approach can be exemplified by the chemical resolution of 4-hydroxy[2.2]paracyclophane (±)-16. 57 This compound has been submitted to a reaction with (1S)-(À)-camphanoyl chloride ((S)-17, Scheme 8) to form a couple of diastereomers, which can be easily separated by silica gel column chromatography (Scheme 8).…”
Section: Phenolsmentioning
confidence: 99%
“…Recently, 26 we have shown that, similarly to phenol 1, the enantiomerically pure compound 12 can be used as a chiral inductor, namely, recoverable auxiliary reactant in the asymmetric allylboronation of benzaldehyde (ee of the product, 3-buten-1-phenyl-1-ol, up to 59%).…”
Section: Synthesis Of Enantiomerically Pure Phanolmentioning
confidence: 99%
“…Colourless, needle-like crystals were obtained from EtOH, C 26 The structures were solved by direct method and refined by the full-matrix least-squares against F 2 in anisotropic (for no-hydrogen atoms) approximation. The H(C) atoms were placed in geometrically calculated positions and were refined in isotropic approximation in riding model with the U iso (H) parameters equal to 1.2 U eq (Ci), for methyl groups equal to 1.5 U eq (Cii), where U(Ci) and U(Cii) are, respectively, the equivalent thermal parameters of the atoms to which the corresponding H atoms are bonded.…”
Section: Crystallographic Analysis Of (S P S)-13mentioning
confidence: 99%